\(\left(\frac{1}{4}x-1\right)+\left(\frac{5}{6}x-2\right)-\left(\frac{3}{8}x+5\right)=3,5\)
\(\Rightarrow\frac{1}{4}x-1+\frac{5}{6}x-2-\frac{3}{8}x-5=\frac{7}{2}\)
\(\Rightarrow\left(\frac{1}{4}+\frac{5}{6}-\frac{3}{8}\right)x+\left[\left(-1\right)+\left(-2\right)+\left(-5\right)\right]=\frac{7}{2}\)
\(\Rightarrow\frac{17}{24}x+\left(-8\right)=\frac{7}{2}\)
\(\Rightarrow\frac{17}{24}x=\frac{7}{2}-\left(-8\right)=\frac{23}{3}\)
\(\Rightarrow x=\frac{23}{2}:\frac{17}{24}=\frac{276}{17}\)
~ Hok tốt ~
1/4x - 1 + 5/6x - 2 - 3/8x - 5 = 3,5
=> (1/4x + 5/6x - 3/8x) - 1 - 2 - 5 = 3,5
=> x. (1/4 + 5/6 - 3/8) - (1 + 2 + 5) = 3,5
=> x . 17/24 - 8 = 3,5
=> x . 17/24 = 3,5 + 8
=> x . 17/24 = 11,5
=> x = 11,5 : 17/24
=> x = 276/17